Peranan Consumer Engagement Sebagai Variabel Mediasi Atas Pengaruh Content Marketing Terhadap Keputusan Pembelian Online Di Era Digital Marketing (Studi Pada Konsumen Brand Fashion Realizm87) - Dewi Oktavia Putri; Rahayu Puji Suci; Mulyono (Bulletin of Management and Business, 2022)
Abstract In this era of globalization or better known as the Industrial Revolution 4.0 Technology trend, digital marketing is the most effective place to increase sales of a brand, and Realizm87 is no exception. This study examines the relationship between three variables, namely content marketing (X) as an independent variable, consumer engagement (Z) as a mediating variable, and online purchasing decisions (Y) as a dependent variable. This research method is quantitative research with descriptive research type. The sampling technique used is non-probability sampling with purposive sampling type. Collecting data by distributing questionnaires to 96 consumers who bought Realizm87 products online. Based on the results of the study, it was found that attractive content marketing will increase consumer engagement and online purchasing decisions. High Consumer Engagement will increase online purchasing decisions. Attractive content marketing through high consumer engagement will improve online purchasing decisions.